University business models in disequilibrium – engaging industry and end users within university technology transfer processes. (3rd April 2017) - McAdam, Maura; Miller, Kristel; McAdam, Rodney
Abstract : This article explores how greater engagement with industry and end users has influenced the University Technology Transfer Business Model. In order to achieve this, they adopted a qualitative methodology which draws upon case study evidence of two case universities located in a particular region. The findings, represented in a conceptual framework depict a hybrid University Technology Transfer Business Model which is in a state of permanent disequilibrium as a result of path dependency and organisational culture. This permanent disequilibrium was found to cause challenges in relation to scarce resource allocation and also impacted upon the willingness and ability of academics to engage with industry and end users throughout the technology transfer process. This article contributes to an emerging stream of research on hybrid business models by identifying the challenges of permanent disequilibrium where multiple and conflicting stakeholder goals compete for legitimacy and scarce resources. From a policy and practitioner viewpoint, this research draws attention to the complexities of university, government, industry and end user (Quadruple Helix stakeholders) engagement and the implications of such on university strategy where conflicting dominant logics can cause challenges with alignment of organisational processes and mechanisms.